Evaluation of Safflower (Carthamus tinctorius) Genotypes for Salt Tolerance - Patil, S G; Srinivas, S; Kumar, m Dinesh; Hebbara, M (Annals of Arid Zone, 2016)
A field experiment was carried out on a saline Vertisol (2.1-30 dS m-l) of Gangavathi to screen eleven safflower genotypes for sail tolerance. The yield of safnower genotypes was correlated with time weighted mean salinity to compute yield maxima (Ym). threshold salinity (EO) and slope (S). A-1. Nira and Manjira were found to perform beller than other genotypes. The performance of A-I was found to be superior over Nira and Manjira as salinity increased from 2.010 12.0 dS m-l. The genotype Manjira which was promising under marginally saline conditions.suffered at higher salinity (beyond 10 dS m-l.